2019
DOI: 10.1155/2019/1528635
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa L. (Black Cumin): A Promising Natural Remedy for Wide Range of Illnesses

Abstract: The seed of Nigella sativa (N. sativa) has been used in different civilization around the world for centuries to treat various animal and human ailments. So far, numerous studies demonstrated the seed of Nigella sativa and its main active constituent, thymoquinone, to be medicinally very effective against various illnesses including different chronic illness: neurological and mental illness, cardiovascular disorders, cancer, diabetes, inflammatory conditions, and infertility as well as various infectious disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
267
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(270 citation statements)
references
References 127 publications
3
267
0
Order By: Relevance
“…It has been suggested that N. sativa can influence the main traits of RA via various procedures [57]. Even though some review papers have been published regarding the medicinal features of N. sativa [58][59][60], to the authorsʼ knowledge, there has not been any review conducted in the area of N. sativa and RA. Therefore, in this research, we aimed to conduct a systematic study on the available literature regarding the effects of N. sativa on RA in clinical, animal and cellular models and possible mechanisms responsible for such effects.…”
Section: A Systematic Review Of the Potential Effects Of Nigella Satimentioning
confidence: 99%
“…It has been suggested that N. sativa can influence the main traits of RA via various procedures [57]. Even though some review papers have been published regarding the medicinal features of N. sativa [58][59][60], to the authorsʼ knowledge, there has not been any review conducted in the area of N. sativa and RA. Therefore, in this research, we aimed to conduct a systematic study on the available literature regarding the effects of N. sativa on RA in clinical, animal and cellular models and possible mechanisms responsible for such effects.…”
Section: A Systematic Review Of the Potential Effects Of Nigella Satimentioning
confidence: 99%
“…Few bioactive compounds extracted from Nigella sativa seeds have been identified, the most important being the thymoquinones [19]. Other phytochemicals from different varieties of Nigella sativa include sterols, saponins, phenolic compounds, various alkaloids, some lipid constituents, and fatty acids, as well as volatile oils of different composition [20]. Furthermore, the most important compounds responsible for seed pigmentation are phytomelanins, high-molecular weight polymers formed by the oxidation of phenols [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the commercial use of these seeds has increased in Southeast Asia due to the presence of important trace elements such as zinc and magnesium, which are beneficial for improving immunity levels. They are therefore helpful in preventing asthma (Shomar, 2012;Yimer et al, 2019).Different extracts of Nigella Sativa have a bronchodilator effect due to different mechanisms of action. The aqueous and macerated extracts of Nigella Sativa show a bronchodilatory effect of this plant due to their calcium channel blocking properties (Boskabady et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%